3-O-sulfo-β-d-galactose moiety of endogenous sulfoglycolipids is a potential ligand for immunoglobulin-like receptor LMIR5. Issue 2 (February 2015) - Phongsisay, Vongsavanh; Iizasa, Ei'ichi; Hara, Hiromitsu; Yamasaki, Sho
Highlights 3-O-sulfo-β-d-galactosylceramide C24:1 (C24:1) is an endogenous sulfoglycolipid. LMIR5 interacts preferentially with C24:1 among various brain glycolipids examined. C24:1-induced MCP1 production is reduced in the absence of adaptor protein DAP12. C24:1 activates transcriptional factor NFAT through DAP12-coupled LMIR5. LMIR5 recognizes the 3-O-sulfo-β-d-galactose moiety.